Partisipasi ibu, tingkat kepatuhan pada Program PMT Pemulihan dan Status Gizi Balita : Studi di Puskesmas Tegal Timur - Purwo Hadi Sutini; Dyah Nur Subandriani; Tutik Wahyuni (Poltekkes Kemenkes Semarang, 2013)
Background : Riskesdas 2010 data showed the number of under-five malnutrition is 13%, 4.9% severe malnutrition, infant short 18.5% and very short 17.17%. While the results of PWS in East Tegal Health Centers by 2011 the number of under-five malnutrition 12.69%, 2.67% severe malnutrition, under-five underweight 1.7% and 0.4% are very slim.Objective : Aim of the study was to determine the association of maternal participation, compliance on food supple Recovery program with nutritional status of children.Method : This research uses the one shot case study method. The subjects of this research are 11 children with thin categories of weight/height and the age among 12 – 35 month. The variable of this research are nutritional status, mother participation, and the compliance level of recovery food supplementary program. The method to measure nutritional status is based on the result anthropometry with weight/height index from z score. Mother participation is known from the interview base on questioner about mother care to give children nutrition consumption. The compliance level of recovery food supplementary program is count from the presentation gap of weight before and after supplementary food consumption. The arrange data of mother participation and compliance do every 10 days along 90 days. The data analyze use Fisher exact and Chi-Square test.Results : There was no relation between mother participation with the compliance level of supplementary food consumption program (p = 0.455). However There was relation between compliance level of recovery food supplementary program and nutritional status (p =0.002)Conclusion : Compliance on food supplementary program is important role in improving nutritional status of children.